Predictors of Discharge to Home after Thrombolytic Treatment in Right Hemisphere Infarct Patients - E-I. Ruuskanen; M. Laihosalo; Je. Kettunen; H. Losoi; L. Nurmi; A-M. Koivisto; P. Dastidar; J. Ollikainen; M. Jehkonen (Journal of Central Nervous System Disease, 2010)
Background The aim of the study was to assess the association between thrombolysis and length of hospital stay after right hemisphere (RH) infarct, and to identify which cognitive functions were predictive of discharge. Methods The study group consisted of 75 acute RH patients. Thirty-three patients had thrombolysis. Neuropsychologicalexaminations were performed within 11 days of stroke onset. The cognitive predictors were visual neglect, visual memory, visual search and reasoning and visuoconstructive abilities. The outcome variable was time from stroke to discharge to home. Results Thrombolysis emerged as a statistically significant predictor of discharge time in patients with moderate/severe stroke (NIHSS ≥5). In the total series of patients and in patients with mild stroke (NIHSS <5), thrombolysiswas not significantly associated with discharge time. Milder visuoconstructive defects shortened the hospital stay of the whole patient group and of patients with moderate/severe stroke. In all patient groups, independence in activitiesof daily living (ADL) was a significant single predictor of a shorter hospital stay. The best combination of predictors for discharge was independence in ADL in the total series of patients and in patients with mild stroke, and thrombolysis and independence in ADL in patients with moderate/severe stroke. Conclusions Thrombolytic treatment was a significant predictor of earlier discharge to home in patients with moderate/severe RH infarct, while cognitive functions had less predictive power.